2012
DOI: 10.1073/pnas.1203972109
|View full text |Cite
|
Sign up to set email alerts
|

Resetting capacity limitations revealed by long-lasting elimination of attentional blink through training

Abstract: As with other cognitive phenomena that are based upon the capacity limitations of visual processing, it is thought that attentional blink (AB) cannot be eliminated, even after extensive training. We report in this paper that just 1 h of specific attentional training can completely eliminate AB, and that this effect is robust enough to persist for a few months after training. Results of subsequent behavioral and functional magnetic resonance imaging (fMRI) experiments indicate that this learning effect is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 31 publications
17
67
1
Order By: Relevance
“…However, if the follicular test session followed the menstrual test session the good performance from the menstrual test session apparently carried over to the follicular test session and women would be likely to continue to perform well in spite of the unfavorable effect of estradiol. This interpretation is well in line with the finding that, if the AB is experimentally eliminated by making T2 color--salient for a limited period of time, the AB will not reoccur when the color--saliency is removed (Choi et al, 2012). The mechanisms underlying the continued good performance for the follicular phase appear however to be different from those reflected in P1 and lag 2 T2 P3 peak latencies, because both measures were longer during the follicular phase than during the menstrual phase irrespective of test order (interactions including cycle phase and test order all F < 0.98, all p > .34).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, if the follicular test session followed the menstrual test session the good performance from the menstrual test session apparently carried over to the follicular test session and women would be likely to continue to perform well in spite of the unfavorable effect of estradiol. This interpretation is well in line with the finding that, if the AB is experimentally eliminated by making T2 color--salient for a limited period of time, the AB will not reoccur when the color--saliency is removed (Choi et al, 2012). The mechanisms underlying the continued good performance for the follicular phase appear however to be different from those reflected in P1 and lag 2 T2 P3 peak latencies, because both measures were longer during the follicular phase than during the menstrual phase irrespective of test order (interactions including cycle phase and test order all F < 0.98, all p > .34).…”
Section: Discussionsupporting
confidence: 70%
“…However, that the AB was not generally larger for the first experimental session argues against the possibility that only test order, and therefore task practice, could be responsible for the observed effect of cycle phase on the AB. In line with this conclusion, for a moderate number of sessions a reduction of the AB is generally not reported (Choi et al, 2012;Kranczioch and Thorne, 2013; but see Taatgen et al, 2009 for some evidence of a potential reduction of the AB at the beginning of an experimental session), though it has been shown that after an average of 15 sessions of the AB task a significant reduction of the AB can be found (Maki and Padmanabhan, 1994). In contrast, a rather consistent finding is an improvement of T2 performance that is however importantly not specific to the AB lag(s) (Kranczioch and Thorne, 2013;Nakatani et al, 2012;Seiffert and DiLollo, 1997).…”
Section: Discussionsupporting
confidence: 51%
“…Such an explanation is consistent with recent research in healthy subjects that the AB can be eliminated by prior exposure to the task under conditions in which T2 is made salient (Choi, Chang, Shibata, Sasaki, & Watanabe, 2012).…”
Section: The Effects Of Anticipated Monetary Reward Versus Feedbacksupporting
confidence: 77%
“…This effect is referred to as lag 1 sparing and it is thought to reflect T1 and T2 being processed together within a single attentional episode (DellʼAcqua, Dux, Wyble, & Jolicoeur, 2012;Wyble, Potter, Bowman, & Nieuwenstein, 2011;Wyble, Bowman, & Nieuwenstein, 2009;Chun & Potter, 1995). fMRI (Choi, Chang, Shibata, Sasaki, & Watanabe, 2012;Kranczioch, Debener, Schwarzbach, Goebel, & Engel, 2005;Marois & Ivanoff, 2005;Marois, Yi, & Chun, 2004;Marcantoni, Lepage, Beaudoin, Bourgouin, & Richer, 2003) and PET (Slagter et al, 2012) explorations have localized AB effects to a frontoparietal network composed of core nodes in the posterior parietal and dorsolateral pFC that support a variety of attention tasks (e.g., Corbetta & Shulman, 2002;Desimone & Duncan, 1995). A set of additional areas have been shown to be susceptible to the AB influence, including striate (Williams, Visser, Cunnington, & Mattingley, 2008) and extrastriate visual areas (e.g., DellʼAcqua, Sessa, Jolicoeur, & Robitaille, 2006;Marois et al, 2004), and subcortical structures (i.e., BG and locus coeruleous), whose roles have been incorporated in neural instantiations of 1 University of Padova, 2 The University of Queensland, 3 AB models (Colzato, Slagter, de Rover, & Hommel, 2011;Hommel et al, 2006;Nieuwenhuis, Gilzenrat, Holmes, & Cohen, 2005).…”
Section: Introductionmentioning
confidence: 99%